Principle of Proportionality as a Reflection of the Theory of Justice and its Application by Judges in the Resolution of Business Contract Disputes - Abdul Rahman; Annisa Khusnur Rosyida; Nur Afifah Aminudin; Saparyanto Saparyanto (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
In the business world, contracts have an important role in shaping the pattern of legal relations between the parties. Every business effort carried out by business actors is essentially a legal step, and this is in the realm of contract law. Business contracts are important instruments to secure the exchange of achievements and as evidence that there is a legal relationship between the parties in carrying out business transactions. Proportional distribution becomes the basis of thought in formulating contracts that are able to accommodate the interests of the parties. The principle of proportionality is a reflection of the Theory of Justice because the perspective of the contractual relationship of the parties combines the concept of equal rights in exchange (achievement-counter achievement) as it is understood that the concept of distributive justice in which it has the meaning of proportional distribution. Judges in resolving disputes using the principle of proportionality means to make reasonable and fair decisions based on the values of equality, freedom, and proportional distribution which cannot be separated from the existence of feasibility, propriety and the principle of accuracy.